The Relationship Between Sanitation of Tableware and Germ Numbers at Indomie Food Stalls (Warmindo) Multatuli Area of Medan City - Cut Iva Aulia; Meutia Nanda (Universitas Ibn Khaldun Bogor, 2023)
Cleanliness of cutlery is a very important part and affects the quality of food and drinks. Poor hygiene of food equipment will have an important role in the growth and proliferation of germs, the spread of disease, and poisoning. Several things must be considered to maintain the condition of cutlery including requirements for cutlery, equipment washing and drying techniques, and sanitation for storing cutlery. The purpose of this study was to determine the relationship between tableware sanitation and germ rates at Indomie (Warmindo) food stalls in the Multatuli area of Medan City. This research method uses cross-sectional. The population in this study were 30 Indomie Food Stalls (Warmindo) and 10 Indomie Food Stalls (Warmindo) were taken which used 3 types of cutlery, namely bowls, spoons, and glasses with certain conditions. Statistical test using chi-square with the help of computer software. The research location was conducted at the Indomie (Warmindo) food stall located on Jln. Multatuli, Kec, Medan Maimun, Medan City, North Sumatra. This study produced a p-value (-) for cutlery sanitation, for cutlery washing techniques (bowl, 0.197) (spoon, 0.053) and (glass, 0.197), for cutlery storage sanitation (bowl, 0.035) (spoon, 0.260) and (cup, 0.429). This study concludes that for the sanitation of cutlery, the result is that there is no relationship between the sanitation of cutlery and the number of germs. For the technique of washing cutlery, the result is that there is no relationship between the technique of washing cutlery and the number of germs, and for the sanitation of storing cutlery in cutlery (bowls) there is a relationship between the sanitation of storing cutlery, and the number of germs, while for spoons and glasses, there is no relationship. between storage sanitation and germ numbers. Suggestions are expected for Indomie Food Stall traders (Warmindo) to always maintain and improve the level of cleanliness in serving food.